STRATEGIES OF AL-QUR'AN HADITH TEACHERS IN INCREASING STUDENTS' LEARNING MOTIVATION AT MAN 2 BOGOR - Azis Mubarok, Abdul; Ikhtiono, Gunawan; Isna Alfaien, Noor (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
In a lesson, students are sometimes bored with monotonous explanations and allude to the learning material of the Qur'an Hadith so that teachers must use strategies so that the learning carried out runs smoothly. The purpose of this study is to find out how the strategy steps of Al-Qur'an Hadith teachers in increasing students' motivation to learn, what factors support and hinder the implementation of Al-Qur'an Hadith teachers' strategies in increasing students' learning motivation, and how effective strategies are applied by Al-Qur'an Hadith teachers in increasing students' learning motivation at MAN 2 Bogor. The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The results of this study are: 1. The strategy of Al-Qur'an Hadith teachers in increasing the learning motivation of students at MAN 2 Bogor is to use various methods such as memorization and exemplary stories. Then the use of media such as Quizizz, Kahoot, PowerPoint and tadarus is added before starting learning. 2. The supporting factor for the implementation of the teacher's strategy is adequate learning facilities. In addition, inhibiting factors are due to lack of meeting hours, lack of interest in learning, and misuse of technology. 3. The effectiveness of the strategies applied by the Qur'an Hadith teacher has an impact on the continuity of effective learning for students